Recent developments in organizational culture and climate research - Ashkanasy, Neal (Henry Stewart Talks, 2012)
Organizational culture, Organizational climate, Multilevel perspectives, Positive management, State-of-the art reviews, Organizational performance, Organizational sustainability, Gossip at work, Strategic human resource management, Organizational identity, Work-Family Conflict, Dynamics and diversity, Organizational theory, International themes, Chinese organizations, Project GLOBE, Ethical climate